2019
DOI: 10.1177/1049909119852082
|View full text |Cite
|
Sign up to set email alerts
|

Ten-Year Trends of Utilization of Palliative Care Services and Life-Sustaining Treatments and Hospital Costs Associated With Patients With Terminally Ill Lung Cancer in the United States From 2005 to 2014

Abstract: Background: Palliative care services and life-sustaining treatments are provided to dying patients with lung cancer in the United States. However, data on the utilization trends of palliative care services and life-sustaining treatments of dying patients with lung cancer are not available. Methods: This study was a retrospective analysis of the National Inpatient Sample data (2005-2014) and included patients with lung cancer, aged ≥ 18 years, who died in the hospitals. Claims data of palliative care services a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
4
27
0
Order By: Relevance
“…We found that only 6.7% of ECC hospitalizations utilized palliative care services between 2007 and 2016, which was much lower than anticipated, and lower than palliative care use for other similar poor prognosis cancers, such as pancreatic and liver cancer, in the US [ 10 ]. However, similar to findings with other diseases [ 5 , 6 , 7 , 22 ], we also found that palliative care utilization significantly reduced hospital charges and LOS for the ECC patients. Reasons for the reductions in hospital charges include the effective management of the symptoms, the performance of fewer aggressive procedures, and shorter stays in the hospital for patients who receive palliative care services [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that only 6.7% of ECC hospitalizations utilized palliative care services between 2007 and 2016, which was much lower than anticipated, and lower than palliative care use for other similar poor prognosis cancers, such as pancreatic and liver cancer, in the US [ 10 ]. However, similar to findings with other diseases [ 5 , 6 , 7 , 22 ], we also found that palliative care utilization significantly reduced hospital charges and LOS for the ECC patients. Reasons for the reductions in hospital charges include the effective management of the symptoms, the performance of fewer aggressive procedures, and shorter stays in the hospital for patients who receive palliative care services [ 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…These charges, as well as significant discomfort, could potentially be avoided by engagement with palliative care [ 1 , 2 ], whereby an expert interdisciplinary team consisting of physicians, nurses, social workers, and other specialties work together to alleviate pain as well as psychological and spiritual distress of patients struggling with terminal diseases [ 3 , 4 ]. Palliative care has been associated with reducing hospital charges and length of hospital stay (LOS) [ 1 , 5 , 6 ] since the management of symptoms avoids unnecessary charges and long hospital stays [ 1 , 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although decreasing annual proportions of advanced age groups and changing proportions of various comorbidities among RF-IMV tracheostomy discharges seem to suggest evolving selection, in the context of our prior analysis, these changes actually seem to reflect changes in the underlying RF-IMV population in general ( 17 ). Finally, another potential factor playing a role in the decreases in tracheostomies among RF-IMV discharges is greater collaboration with palliative care physicians and earlier initiation of goals of care discussion that preclude decisions to perform tracheostomy in this population ( 18 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…This important finding reflects the growing body of literature that suggests earlier palliative care consultation may correspond to decreased LOS, especially in ICU patients. 10 Although a common perception is that earlier palliative care consultation decreases LOS by guiding family or legal representatives to withdraw of life-sustaining therapy earlier in the hospital course, chi-square analysis (Table 2) showed that hospital mortality was not associated with early or late palliative care consultation. To our knowledge, this study is the first to demonstrate this association, specifically in the neurosurgical population.…”
Section: Discussionmentioning
confidence: 99%